Population genetic and phylogenetic analysis of pupfish (Cyprinodon, Cyprinodontidae) in the Rio Conchos and adjacent rivers reveals hidden diversity - Casey Ernest; Michael Tobler; Ma. Lourdes De Lozano-Vilano; Mauricio De La Maza-Benignos; Tracy A. Diver; Wade D. Wilson; Thomas F. Turner; Evan W. Carson (Conservation Genetics, 2026)

Development of eighteen novel microsatellite loci for Masked Bobwhite, Colinus virginianus ridgwayi - Steven M. Mussmann; Wade D. Wilson (Molecular Biology Reports, 2024)

Genetic detection and population structure of a non-native hybridogenic Poeciliopsis species in the Santa Cruz River of Arizona, USA - Steven M. Mussmann; Doug Duncan; Kent R. Mosher; William T. Stewart; Peter N. Reinthal; Wade D. Wilson (Biological Invasions, 2024)

Development of twenty-one novel microsatellite loci for Gila topminnow, Poeciliopsis occidentalis occidentalis - Steven M. Mussmann; Alexis S. Harrison; Wade D. Wilson (Molecular Biology Reports, 2023)

Geographic distribution of genetic diversity in populations of Rio Grande Chub Gila pandora - René Galindo; Wade D. Wilson; Colleen A. Caldwell (Conservation Genetics, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Isolation and characterization of twenty-five novel microsatellite loci in Colorado pikeminnow, Ptychocheilus lucius, with cross-species amplification for eight other cyprinids - Renee M. Martin; Morgan L. Robinson; Wade D. Wilson (Conservation Genetics Resources, 2015)

Isolation and characterization of eight novel microsatellite loci in endangered Wyoming toad, Bufo baxteri - Renee M. Martin; Connie L. Keeler-Foster; Kenneth G. Boykin; Gerard Zegers; Wade D. Wilson (Conservation Genetics Resources, 2012)

Introgressive hybridization of human and rodent schistosome parasites in western Kenya - MICHELLE L. STEINAUER; BEN HANELT; IBRAHIM N. MWANGI; GEOFFREY M. MAINA; LELO E. AGOLA; JOSEPH M. KINUTHIA; MARTIN W. MUTUKU; BEN N. MUNGAI; WADE D. WILSON; GERALD M. MKOJI; ERIC S. LOKER (Molecular Ecology, 2008)
Hybridization and introgression can have important consequences for the evolution, ecology and epidemiology of pathogenic organisms. We examined the dynamics of hybridization between a trematode parasite of humans, Schistosoma mansoni , and its sister species, S. rodhaini , a rodent parasite, in a natural hybrid zone in western Kenya. Using microsatellite markers, rDNA and mtDNA, we showed that hybrids between the two species occur in nature, are fertile and produce viable offspring through backcrosses with S. mansoni . Averaged across collection sites, individuals of hybrid ancestry comprised 7.2% of all schistosomes collected, which is a large proportion given that one of the parental species, S. rodhaini, comprised only 9.1% of the specimens. No F1 individuals were collected and all hybrids represented backcrosses with S. mansoni that were of the first or successive generations. The direction of introgression appears highly asymmetric, causing unidirectional gene flow from the rodent parasite, S. rodhaini, to the human parasite, S. mansoni. Hybrid occurrence was seasonal and most hybrids were collected during the month of September over a 2‐year period, a time when S. rodhaini was also abundant. We also examined the sex ratios and phenotypic differences between the hybrids and parental species, including the number of infective stages produced in the snail host and the time of day the infective stages emerge. No statistical differences were found in any of these characteristics, and most of the hybrids showed an emergence pattern similar to that of S. mansoni. One individual, however, showed a bimodal emergence pattern that was characteristic of both parental species. In conclusion, these species maintain their identity despite hybridization, although introgression may cause important alterations of the biology and epidemiology of schistosomiasis in this region.

Coccidia (Apicomplexa: Eimeriidae) in the Primates and the Scandentia - Donald W. Duszynski; Wade D. Wilson; Steve J. Upton; Norman D. Levine (International Journal of Primatology, 1999)

Organochlorine Pesticides and Polychlorinated Biphenyls (PCBs) in Sediments and Biota from Four US Arctic Lakes - S. M. Allen-Gil; C. P. Gubala; R. Wilson, D. H. Landers; T. L. Wade; J. L. Sericano; L. R. Curtis (Archives of Environmental Contamination and Toxicology, 1997)